2001
DOI: 10.1023/a:1011513223894
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Aging of the human skeleton is characterized by decreased bone formation and bone mass and these changes are more pronounced in patients with osteoporosis. As osteoblasts and adipocytes share a common precursor cell in the bone marrow, we hypothesized that decreased bone formation observed during aging and in patients with osteoporosis is the result of enhanced adipognesis versus osteoblastogenesis from precursor cells in the bone marrow. Thus, we examined iliac crest bone biopsies obtained from 53 healthy nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
304
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 739 publications
(340 citation statements)
references
References 37 publications
8
304
1
2
Order By: Relevance
“…Because PI in general show a high degree of protein binding (for LPV, up to 99% of the inhibitor are bound to serum protein), this corresponds to available protein-free inhibitor concentrations in the low nanomolar range (summarized in Ref. 39). Furthermore, drug levels in clinically relevant HIV reservoirs can differ from those reflected in the plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Because PI in general show a high degree of protein binding (for LPV, up to 99% of the inhibitor are bound to serum protein), this corresponds to available protein-free inhibitor concentrations in the low nanomolar range (summarized in Ref. 39). Furthermore, drug levels in clinically relevant HIV reservoirs can differ from those reflected in the plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…osteoporosis, glucocorticoid, or glitazone therapy) (52). Because osteoblasts and adipocytes arise from MSC in the bone marrow microenvironment, understanding the "switching mechanisms" between osteoblast versus adipocyte differentiation can provide novel therapeutic targets for enhancing bone formation (52,53). Previous studies have identified some factors that play a role in the switching mechanism.…”
Section: T253mentioning
confidence: 99%
“…It has been suggested that the osteogenic and adipogenic differentiation of hMSCs are two inverse processes, with one process inhibiting the other (36). Furthermore, in osteoporotic patients, the number of adipocytes was increased in the marrow, implying a change of cell fate disposition from osteoblast lineage to adipocyte lineage (37,38). We therefore examined the effect of our hit siRNAs on adipogenic differentiation of hMSCs by combined treatment with an adipogenic inducing mixture [100 g/ml 3-isobutyl-1-methylxanthine (IBMX)/1 M dexamethasone/10 g/ml insulin].…”
Section: High-throughput Sirna Screen In Hmscsmentioning
confidence: 99%